2021
DOI: 10.3390/socsci10110408
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Knowledge and Attitudes towards Plastic Pollution among the Youth in Nairobi, Kenya

Abstract: Kenya has made many attempts to regulate the production of single-use plastics through partial bans and the imposition of hefty taxes. Whereas government initiatives are crucial to resolving single-use plastic pollution, commitments made by youths can be an important part of the solution. Yet, youths are habituated to using single-use plastics without understanding fully their negative impacts. Understanding the knowledge and attitudes of youths is of the utmost importance in the effort to turn the tide agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The majority of the respondents expressed their desire to prefer to reusable alternatives (94.8%) and pay extra for their use (73%). Cloth bags, reusable food containers, paper bags, and glass water cans were the most preferred environmentally friendly packaging materials and alternatives [ 8 , 27 ]. The present study also illustrates that more than 60% of tourists support that shopkeeper shares polyethylene to customers for free of cost, whereas they ask charges for the paper carry bags.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the respondents expressed their desire to prefer to reusable alternatives (94.8%) and pay extra for their use (73%). Cloth bags, reusable food containers, paper bags, and glass water cans were the most preferred environmentally friendly packaging materials and alternatives [ 8 , 27 ]. The present study also illustrates that more than 60% of tourists support that shopkeeper shares polyethylene to customers for free of cost, whereas they ask charges for the paper carry bags.…”
Section: Resultsmentioning
confidence: 99%
“…In concordance to this finding, the reports from multiple studies; most of the participants in different countries were concerned about the effects of plastic waste on health and the environment. [42][43][44][45] Plastics can cause serious health problems due to chemical reactions in plastic materials and food items that generate carcinogenic substances. 46 In the current survey, 60.0% of the participants appreciated the significant roles of mass media in raising the awareness of the public and disseminating the information about the risk of plastic use and its wastes, followed by the role of the educational school materials (27.8%), the outcome of other research also observed the same, where they described that certainly, media is the most common source of information.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were also seen in a South African study, where 42% of the respondent's obtained information on plastic food packaging from informal sources (e.g., friends, family, media, and the internet) [35]. A study in Kenya also showed similar numbers: social media (36%), TV (29%), and radio (15%) were the main media channels through, which the youth acquired knowledge about plastic's impacts on the environment and human health [14].…”
Section: Sociodemographic Background Of Respondentsmentioning
confidence: 92%
“…Awareness of the negative impact of plastic use can be improved with additional knowledge about the correct foodgrade plastics [13]. Proper channels, such as social media can disseminate better knowledge on single-use plastics as a severe environmental issue [14]. Sociodemographic factors, such as age, education level, gender and occupation may influence solid waste management behaviour [15].…”
Section: Introductionmentioning
confidence: 99%